Inter-racial marriages and relationships in the movies of the sixties - Csuti, Edina (AMERICANA E-journal of American Studies in Hungary, 2018)
The article surveys the representation of the intermarriage between a black man and a white woman in Stanley Kramer’s movie titled Guess Who’s Coming to Dinner and investigates on the film’s undoing of racial stereotypes during the controversial 1960s in America by discussing the socio-political and filmic context of the sixties and the regulations on the film industry by the Production Code Administration in that decade. The major part of the research centers on three perspectives: the first is the representation of race, the second is the portrayal of gender, and the third is the analysis of Guess Who’s Coming to Dinner in the light of other movies of the era.